RESPON TANAMAN PAPRIKA TERHADAP KOMBINASI PUPUK KANDANG AYAM DAN NPK PADA TANAH ALUVIAL - Lea Sabrina; Nurjani Nurjani; Setia Budi (Fakultas Pertanian Universitas Tanjungpura, 2020)
This study aim to determined knowing response of paprika plants to the combination manure fertilizer and NPK at alluvial soil. This study held on march, 03 2019 until may, 19 2019 at experimental garden Agriculture’s Faculty of Tanjungpura University. This study used Randomized Completely Design (RCD) with single factor that consist of 6 treatments with 4 replication and 4 samples. The treatments are, A= 1,75 g NPK without manure fertilizer, B= manure fertilizer 50 g + NPK 1,5 g, C= manure fertilizer 100 g + NPK 1,25g, D= manure fertilizer 150 g + NPK 1,25 g, E= manure fertilizer 200 g + NPK 1 g, F= manure fertilizer 250 g without NPK. Observing variable on this study are height of plant, wet weight of plant, dried weight of plant, volume of root plant, weight of fruit, fruit weight of plant, and number of plant. According to the result of this study, the conclusion is combination between manure fertilizer and NPK gave good response to the height of plant and the best dosis cannot found at combination of manure fertilizer and NPK to the paprika’s growth and yield. Key Words: alluvial, manure fertilizer, NPK, paprika